An Assessment of Corporate Social Responsibility Disclosure Frameworks Adopted for Integrated Reporting: Perspectives from Zimbabwe Stock Exchange Listed Firms - Simon, Chosani; Gani, Shenaaz (The Journal of Accounting and Management, 2025)
The objective of this paper is to assess corporate social responsibility (CSR) disclosure frameworks adopted by firms listed on the Zimbabwe Stock Exchange (ZSE). It builds from extant literature that seeks standardisation of nonfinancial reporting in annual reports as a means towards integrated reporting. The study is based on an inductive approach in which qualitative data was collected from annual reports of Zimbabwe Stock Exchange listed firms through content analysis of published annual reports. The results reveal that firms listed on the ZSE refer to different frameworks in reporting CSR activities in their annual reports, leading to variability and inconsistences in CSR disclosures thereby affecting informed decision making. The study therefore recommends adoption of a single hybrid set of CSR disclosure framework by all ZSE listed firms so as to ensure consistency and comparability of financial reports for easier decision making. The study informs policymakers such as accounting regulatory authorities to advocate for the development and adherence to the same CSR disclosure framework that ensures all listed firms’ disclosure adequate CSR information for the benefit of prospective investors and other interested stakeholders. This study provides practical value by highlighting the various CSR frameworks adopted by ZSE listed firms resulting to inconsistent and variability in reporting CSR practices. It further informs firm managers and policymakers to take corrective action in guiding adequate disclosure of CSR information in annual reports.